Which training intensity distribution intervention will produce the greatest improvements in maximal oxygen uptake and time-trial performance in endurance athletes? A systematic review and network meta-analysis of individual participant data - Rosenblat, M. A.; Watt, J. A.; Arnold, J. I.; Treff, G.; Sandbakk, Ø. B.; Esteve-Lanao, J.; Festa, L.; Filipas, L.; Galloway, S. D.; Muñoz, I.; Ramos-Campo, D. J.; Schneeweiss, P.; et al. (Sports Medicine, 2025)
Background: Endurance athletes tend to accumulate large training volumes, the majority of which are performed at a low intensity and a smaller portion at moderate and high intensity. However, different training intensity distributions (TID) are employed to maximize physiological and performance adaptations. Objective: The objective of this study was to conduct a systematic review and network meta-analysis of individual participant data to compare the effect of different TID models on maximal oxygen uptake (VO2max) and time-trial (TT) performance in endurance-trained athletes. Methods: Studies were included if: (1) they were published in peer reviewed academic journals, (2) they were in English, (3) they were experimental or quasi-experimental studies, (4) they included trained endurance athletes, (5) they compared a polarized (POL) TID intervention to a comparator group that utilized a different TID model, (6) the duration in each intensity domain could be quantified, and (7) they reported VO2max or TT performance. Medline and SPORTDiscus were searched from inception until 11 February 2024. Results: We included 13 studies with 348 (n = 296 male, n = 52 female) recreational (n = 150) and competitive (n = 198) endurance athletes. Mean age ranged from 17.6 to 41.5 years and VO2max ranged from 46.6 to 68.3 mL·kg-1·min-1, across studies respectively. Based on the time in heart rate zone approach, there was no difference in VO2max (SMD = - 0.06, p = 0.68) or TT performance (SMD = - 0.05, p = 0.34) between POL and pyramidal (PYR) interventions. There were no statistically significant differences between POL and any of the other TID interventions. Subgroup analysis showed a statistically significant difference in the response of VO2max between recreational and competitive athletes for POL and PYR (SMD = - 0.63, p < 0.05). Competitive athletes may have greater improvements to VO2max with POL, while recreational athletes may improve more with a PYR TID. Conclusions: Our results indicate that the adaptations to VO2max following different TID interventions are dependent on performance level. Athletes at a more competitive level may benefit from a POL TID intervention and recreational athletes from a PYR TID intervention.